Bioseparations science and engineering - Harrison, Roger G., 1944-; Todd, Paul, 1936-; Rudge, Scott R.; Petrides, Demetri P. (Oxford University Press, 2015)
Designed for undergraduates, graduate students, and industry practitioners, Bioseparations Science and Engineering fills a critical need in the field of bioseparations. Current, comprehensive, and concise, it covers bioseparations unit operations in unprecedented depth. In each of the chapters, the authors use a consistent method of explaining unit operations, starting with a qualitative description noting the significance and general application of the unit operation. They then illustrate the scientific application of the operation, develop the required mathematical theory, and finally, descr.
Preceded by: Bioseparations science and engineering / Roger G. Harrison [and others]. ©2003.
Keywords: Biomolecules -- Separation.; Biochemical engineering.; Separation (Technology); Extraction (Chemistry); elektronické knihy; electronic books